Heat transfer enhancement investigation in jet impingement system of a single and array of square jets using numerical tools - Allauddin, Usman; Sohail, Muhammad U.; Sohaib, Muhammad; Siddiqui, Muhammad A.; Khan, Muhammad H. U.; Khan, Kashif; Verdin, Patrick G. (Begell House, 2023)
Computational Fluid Dynamics (CFD) techniques can predict complex fluid flow structures and the thermal performance of jet impingement systems. Numerical studies can complement extensive and time-consuming experimental studies, where local parameter measurements are difficult and costly to obtain. In the current work, a single and an array of four and nine square jets impingements were numerically investigated with CFD, for mass flow rate (m) ranging from 2.71x10-4to 7.40x10-4kg/s. The effects of the jet’s outlet-to-target plate distance (Z) were assessed as a function of the width of a single square nozzle (B). The flow field features of different nozzle configurations were also studied. It was shown that the Nusselt number increases as the mass flow rate increases, but increases inversely as the dimensionless jet’s outlet-to-target plate spacing Z/B increases. The numerical investigation also demonstrated that when increasing the number of nozzles under a constant mass flow rate, the Nusselt number significantly increases. The effect of nozzle configuration is not that significant at Z/B > 7. The present impinging jet system offers about 63% enhancement in thermal efficiency was found while the pumping power increased by 3.7 times. All simulations were successfully validated with experimental data.
Keywords: Jet impingement; square jet; heat transfer; turbulence modeling; RANS